2006
DOI: 10.1093/ejo/cjl048
|View full text |Cite
|
Sign up to set email alerts
|

In vitro toxicity evaluation of silver soldering, electrical resistance, and laser welding of orthodontic wires

Abstract: The long-term effects of orthodontic appliances in the oral environment and the subsequent leaching of metals are relatively unknown. A method for determining the effects of various types of soldering and welding, both of which in turn could lead to leaching of metal ions, on the growth of osteoblasts, fibroblasts, and oral keratinocytes in vitro, is proposed. The effects of cell behaviour of metal wires on osteoblast differentiation, expressed by alkaline phosphatase (ALP) activity; on fibroblast proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 18 publications
2
38
0
3
Order By: Relevance
“…These results are similar to those from previous studies. 10,14,18 Sestini et al 18 reported that laser welding was the only bonding method that was well tolerated by cells, whereas silver soldering was evaluated as highly toxic for all cell types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are similar to those from previous studies. 10,14,18 Sestini et al 18 reported that laser welding was the only bonding method that was well tolerated by cells, whereas silver soldering was evaluated as highly toxic for all cell types.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the few existing toxicity studies that compared laser welding and silver soldering methods support this result. [10][11][12][13][14][15][16][17][18] Sestini et al 18 noted that laser welding was the only well-tolerated bonding method, whereas silver soldering was highly toxic to all types of cells. Bagatin et al 19 used scanning electron microscopy (SEM) and energy dispersive x-ray spectroscopy in an in vivo study in which they investigated the corrosion of silver soldered Haas expanders in patients using antimicrobial agents.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] The metal parts that remain in the oral cavity are subject to corrosion because this environment's physical properties, ie, the chemical and microbiological properties, stimulate the dissolution of metals. [8][9] Among the cations present in the alloys, gold and palladium (noble elements) may not be detected, whereas silver, copper, zinc, and gallium are always found. 3,8 According to the International Register of Potentially Toxic Chemicals of the United Nations Environment Program, metallic ions such as cadmium, copper, silver, and zinc are present in silver soldering Use an amalgam carrier with a 2-mm-diameter opening to determine the disk width.…”
Section: Introductionmentioning
confidence: 99%
“…5 In conventional dental brazing -defined as soldering over a temperature of 450°C -the parent metals are joined with different types of metals, which may reduce corrosion resistance because of galvanic corrosion between metals. [6][7][8] The high corrosion rates can influence the biocompatibility [9][10][11] and mechanical strength. 9 Laser welding using a pulsed Nd:YAG (neodymium-doped yttrium aluminium garnet; Nd:Y3Al5O12) laser is a current technology and has been developed for joining purposes in the dental laboratory and offers clear-cut advantages compared to the various soldering methods.…”
Section: Introductionmentioning
confidence: 99%